15 seconds ebook A novel. - Gross, Andrew (2012)
"A total white knuckle, stay-up-all-night thrill ride. Enjoyed the heck out of it!" —Harlan Coben "A top-notch thriller writer." —Chicago Sun Times "A master of no-nonsense, good, old-fashioned suspense." —Steve Berry, New York Times bestselling author of The Jefferson Key A writer "in the company of Child and Coben" (Connecticut Post), New York Times bestseller Andrew Gross is the acclaimed author of The Blue Zone, Eyes Wide Open, and other exceptional suspense thrillers. Now, with 15 Seconds, he delivers an electrifying, lightning-paced story of a desperate man on the run, trying to save his family from the faceless enemy that's determined to destroy them all. A gripping tale of a life turned upside-down in 15 Seconds, Gross's stunner is a must for fans of James Patterson, David Baldacci, Jeffery Deaver, Lisa Gardner, Nelson DeMille, Tess Gerritsen, or anyone who likes action and suspense done to perfection.